Parent Perceptions of Social Behaviors Associated With Autism Spectrum Disorder Are Related to Motor Skills. (May 2020) - Gladfelter, Allison; Johnson, Erik; Odeh, Christina
Parents who report motor difficulties as their primary concern receive autism intervention services earlier than those first concerned with communication. This study revealed that parent perceptions of their child's social responsiveness correlated with standardized scores of motor proficiency. Promoting awareness of this relationship could lead parents to seek services sooner.